BIO-EFFICACY OF THE LEAVES EXTRACTS OF HYPTIS SUAVEOLENS (L.) POIT AGAINST THE FISH PATHOGENS : Life Science-Microbiology - JOY JEBA MALAR T, RENISHEYA; SUSHNA S L; JOHNSON M; JANAKIRAMAN N; JOY JEBA ETHAL T, RENOLA (International Journal of Life Science and Pharma Research, 2012)
The objective of the present study is to investigate the bioefficacy of the leaves extracts of Hyptis suaveolens (L.) Poit against the fish pathogens isolated from diseased Tilapia (Oreochromis niloticus). The petroleum ether, ethanol, ethyl acetate, chloroform and aqueous extracts of H. suaveolens were tested against viz., Aeromonas formicans, Aeromonas hydrophila, Bacillus subtilis, Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa by the agar well diffusion method. Different extracts of H. suaveolens showed the zone of inhibition against the isolated pathogens. The results of ethanolic extracts of H. suaveolens demonstrated broad spectrum of activities that inhibited the growth with the maximum zone of inhibition 21 mm for B. subtilis (100 µg/mL), 21 mm for P. aeruginosa (75 µg/mL), 17 mm for K. pneumonia (100 µg/mL) and 21 mm for E. coli (75 µg/mL). The results of the ethyl acetate extracts of H. suaveolens illustrated the widest spectrum activities with the maximum zone of inhibition 23 mm for A. formicans (75 µg/mL), 16 mm for A. hydrophilia (100 µg/mL), 13 mm for B. subtilis (75 µg/mL) and 21 mm for P. aeruginosa (100 µg/mL).The double distilled water extracts of H. suaveolens showed zero percent of inhibition against the pathogens viz., B. subtilis, K. pneumonia and P. aeruginosa. The result of the present study gives more opportunity to screen the phytoconstituents which will be very functional to combat the various diseases caused by pathogenic bacteria